METHANISATION IN AGRICULTURE: ECONOMIC, ENVIRONMENTAL, SOCIAL BENEFITS AND INTERNATIONAL EXAMPLES - Petia BRANZOVA; Annie DIMITROVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Methanisation is the process of anaerobic digestion of organic materials, including animal manure and plant residues, resulting in the production of biogas. In agriculture, methanisation provides sustainable waste management solutions, reduces the carbon footprint and contributes to energy independence for farmers. This article explores the economic, environmental and social benefits of methanation, presenting detailed examples from Germany, France, Bulgaria, Italy and Sweden where this technology has been successfully implemented at different levels. It highlights the challenges of using methanisation, namely high initial costs and the need for regulatory support. It also looks at prospects for future development, such as the establishment of cooperative structures for centralised methanisation, the expansion of financing and opportunities for integration with other renewable energy technologies. The findings show that methanisation is a key to sustainable agricultural development and has the potential to reach new areas with appropriate policy and financial support.